Cohorts as collections of bodies and communities of persons: insights from the SEARCH010/RV254 research cohort. Issue 6 (9th November 2020) - Henderson, Gail E; Rennie, Stuart; Corneli, Amy; Peay, Holly L
Abstract: Longitudinal research cohorts are uniquely suited to answer research questions about morbidity and mortality. Cohorts may be comprised of individuals identified by specific conditions or other shared traits. We argue that research cohorts are more than simply aggregations of individuals and their associated data to meet research objectives. They are social communities comprised of members, investigators and organizations whose own interests, identities and cultures interact and evolve over time. The literature describes a range of scientific and ethical challenges and opportunities associated with cohorts. To advance these deliberations, we report examples from the literature and our own research on the Thai SEARCH010/RV254 cohort, comprising individuals diagnosed with human immunodeficiency virus (HIV) during acute infection. We reflect on the impact of cohort experiences and identity, and specifically how people incorporate cohort participation into meaning making associated with their diagnosis, the influence of cohort participation on decision making for early-phase clinical trials recruited from within the cohort, and the impact of the relationships that exist between researchers and participants. These data support the concept of cohorts as communities of persons, where identity is shaped, in part, through cohort experiences. The social meanings associated with cohorts have implications for the ethics of cohort-based research, as social contexts inevitably affect the ways that ethical concerns manifest.